circRNA_BMPR2 affects the progression of polycystic ovary syndrome by regulating the expression of Rab43 - Wang Liping; Tao Chenyue; Chen Shuai; Gui Liu; Zhang Yitong; Jiang Min; Zhou Dongjie; Zhou Luojing (Gynecological Endocrinology, 2025)
Polycystic Ovary Syndrome (PCOS) is a common reproductive and metabolic disorder causing infertility in women of childbearing age.Circular RNAs are known to be involved in PCOS development, but their regulatory mechanisms remain unclear. This study explored the role of circ_BMPR2 in PCOS to advance early diagnosis and treatment.It found elevated circ_BMPR2 expression in ovarian granulosa cells of PCOS patients. Knocking down of circ_BMPR2 inhibited proliferation and promoted apoptosis in KGN cell. Mechanistically, we confirmed that circ_BMPR2 acts as a sponge to bind miR-619-5p, which could specifically target Rab43 gene.PCOS tissues showed upregulated Rab43, and silencing circ_BMPR2 reduced Rab43 levels, rescued by a miR-619-5p inhibitor. Further experiments confirmed that overexpression of Rab43 reversed the effects of circ_BMPR2 knockdown on cell proliferation and apoptosis in KGN cells. Thus,our findings implicate circ_BMPR2 acts as a key player in PCOS process, by modulating growth and cell cycle progression of GCs through regulating the miR-619-5p/Rab43 axis. This suggests that circ_BMPR2 could be a prospective biomarker for the early diagnosis of PCOS. By understanding its molecular mechanisms, we can pave the way for more effective interventions to treat this complex disease.